Does it pay to bribe? The influence of bribery on new venture disbanding in China. (April 2021) - Tang, Jintong; Tang, Zhi
This research extends bribery research toward entrepreneurial theory and practice by examining how bribery impacts new venture disbanding in China. Existing research suggests that bribery may enhance firms' competitive advantage; however, building off of resource-based view and taking into consideration the institutional context in China, the current study proposes that firm bribery activity hurts new ventures by increasing the hazard of venture disbanding. Further, guided by resource dependence theory, this study examines how local economic development and organizing activity moderate the relation between bribery and disbanding. In particular, it is proposed that when local economic development is suffering, or when firms are not engaging in appropriate organizing activities, bribery will lead to higher chance of new venture disbanding. Data from Chinese entrepreneurs support these hypotheses.